Repositories, data dictionaries, and encyclopedias for SQL/DS - Eaton, Roger G. (My University, 2016)
Justified Confusion and wonderment exists about the support of repositories, data dictionaries, and encyclopedias for the SQL/DS platform. In my role as an SQL/DS DBA, I was obliged to design and develop my own data dictionary. During the process, I developed an understanding of the various genre of development support databases. At their highest level of definition, reposi tories, encyclopedias, and data dictionaries are databases that support applications development. I may get some argument about this definition from business data modeling people, but hey, most of us are paid to deliver business systems. A business model is only valuable (to most of us, anyway) if it leads to a business solution. Thus, I refer to repositories, encyclopedias, and data dictionaries as applications-development support databases. For our purposes, let's agree that designing a business model is part of the applications-development process.
Citation: Eaton, R. (1993). Repositories, data dictionaries, and encyclopedias for SQL/DS. DATABASE Programming & Design, 6(6) 21-22
Keywords: SQL/DS; Repositories; Data Dictionaries; Relational Databases; Encyclopedias